Gambaran Epidemiologi Kasus Tumor Meningioma Intrakranial WHO Derajat II dan III di Rumah Sakit Kanker Dharmais - Singh, Arwinder; Firdaus, Muhammad; Widarta, Oskar Ady; Sugiarto, Yosafat Kurniawan; Halim, Danny; Faried, Ahmad (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Meningioma is the most common primary intracranial tumors in adults. Although most meningioma cases are regarded as benign, certain types have been suggested of having higher proliferative capacities compared to the majority. Knowing the epidemiology of the more aggressive types of meningioma are important to anticipate the disease burden and improve their management.  This study aims to describe the epidemiology of WHO grade II and III intracranial meningiomas at Dharmais National Cancer Center Hospital. All patients diagnosed with WHO grade II or III intracranial meningiomas between 2011 and 2022 were included in this study. Information on patient’s characteristics, tumor location, and histopathological analyses. As many as thirty-three patients diagnosed with WHO grade II and III intracranial meningiomas between 2011 and 2022. Most patients were female (72.72%), aged between 40- to 60-year-old (57.57%), classified as WHO grade II (60.6%), and had their tumors located at convexity regions (48.48%). The most common grade II intracranial meningioma is atypical (95%), while the majority of grade III intracranial meningiomas is anaplastic (76.92%). In both WHO grade II and III intracranial meningiomas, the highest number of patients aged between 40- to 60-year-old, 60% and 53.85%, respectively. Interestingly, most WHO grade II intracranial meningiomas were in skullbase regions (50%); meanwhile, majority of WHO grade III intracranial meningiomas were in convexity regions (69.23%). Although it only represents a minor fraction from the total meningioma cases, patients who are diagnosed with WHO grade II and III intracranial meningiomas are faced with higher risks of morbidity and mortality compared to WHO grade I intracranial meningiomas. The results of this study describe the current epidemiology of this challenging tumor. Keywords : Intracranial, Meningioma, Benign, WHO Grading ABSTRAK Meningioma adalah tumor intrakranial yang paling sering terjadi pada pasien dewasa. Meskipun kebanyakan kasus meningioma intrakranial tergolong jinak, namun beberapa tipe meningioma tertentu terbukti memiliki kapasitas proliferatif yang lebih tinggi dibandingkan dengan mayoritas tipe meningioma. Pengetahuan mengenai epidemiologi dari tipe meningioma yang bersifat agresif sangatlah penting untung mengetahui beban penyakit dan melakukan upaya peningkatan manajemen penyakit ini. Penelitian ini bertujuan untuk mengetahui data epidemiologi meningioma intrakranial derajat 2 dan 3 berdasarkan klasifikasi histopatologis yang ditetapkan oleh badan kesehatan dunia / World Health Organization (WHO). Seluruh pasien yang didiagnosis dengan meningioma intrakranial derajat 2 dan 3 di RS Kanker Dharmais selama periode tahun 2011 s.d. 2022 dimasukkan ke dalam studi ini. Data mengenai karakteristik pasien, lokasi tumor, dan hasil analisis histopatologis diambil dan diolah sebagai data penelitian. Sebanyak 33 pasien didiagnosis dengan meningioma intrakranial derajat 2 dan 3 selama periode tahun 2011 s.d. 2022. Mayoritas pasien adalah perempuan (72.72%), berusia antara 40 s.d. 60 tahun (57.57%), didiagnosis dengan meningioma intrakranial derajat 2 (60.6%), dengan lokasi tumor di daerah konveksitas (48.48%). Jenis meningioma derajat 2 tersering adalah atipikal (95%), sedangkan jenis meningioma derajat 3 tersering adalah anaplastik (76.92%). Rentang usia terbanyak dari pasien penderita meningioma intrakranial derajat 2 (60%) dan 3 (53.85%) adalah 40 s.d. 60 tahun. Dalam hal lokasi tumor, lokasi tumor tersering dari meningioma derajat 2 adalah dasar tengkorak (50%), sedangkan lokasi tumor tersering dari meningioma derajat 3 adalah konveksitas (69.23%). Meskipun mayoritas pasien yang didiagnosis dengan meningioma intrakranial tergolong sebagai derajat 1, namun pasien meningioma intrakranial derajat 2 dan 3 memiliki resiko morbiditas dan mortalitas yang lebih tinggi. Hasil dari penelitian ini memaparkan data epidemiologi terkini dari jenis meningioma intrakranial yang terbilang lebih agresif. Kata Kunci: Meningioma, Intrakranial, Jinak, Derajat WHO